Meeting user needs in national healthcare systems: lessons from early adopter community pharmacists using the electronic prescriptions service. - Harvey, J; Avery, A; Hibberd, R; Barber, N (BioMed Central, 2014)
BACKGROUND: The Electronic Prescription Service release Two (EPS2) is a new national healthcare information and communication technology in England that aims to deliver effective prescription writing, dispensing and reimbursement service to benefit patients. The aim of the study was to explore initial user experiences of Community Pharmacists (CPs) using EPS2. METHODS: We conducted nonparticipant observations and interviews in eight EPS2 early adopter community pharmacies classified as 'first-of-type' in midlands and northern regions in England. We interviewed eight pharmacists and two dispensers in addition to 56 hours recorded nonparticipant observations as field notes. Line-by-line coding and thematic analysis was conducted on the interview transcripts and field notes. RESULTS: CPs faced two types of challenge. The first was to do with missing electronic prescriptions. This was sometimes very disrupting to work practice, but pharmacists considered it a temporary issue resolvable with minor modifications to the system and user familiarity. The second was to do with long term design-specific issues. Pharmacists could only overcome these by using the system in ways not intended by the developers. Some felt that these issues would not exist had 'real' users been involved in the initial development. The issues were: 1) printing out electronic prescriptions (tokens) to dispense from for safe dispensing practices and to free up monitors for other uses, 2) logging all dispensing activities with one user's Smartcard for convenience and use all human resources in the pharmacy, and, 3) problematic interface causing issues with endorsing prescriptions and claiming reimbursements. CONCLUSIONS: We question if these unintended uses and barriers would have occurred had a more rigorous user-centric principles been applied at the earlier stages of design and implementation of EPS. We conclude that, since modification can occur at the evaluation stage, there is still scope for some of these barriers to be corrected to address the needs, and enhance the experiences, of CPs using the service, and make recommendations on how current challenges could be resolved.